After in defence of the school: an interview with jan masschelein and maarten simons - Alexandre Filordi de Carvalho; Julio Groppa Aquino (Universidade Estadual de Campinas, 2017)
The intent of the interview with the authors of In defence of the school was debating the reception of such book in the context of educational research in Brazil. On one hand, the very outreach of the idea of defending the school was inquired, taking into account the socio-historical context which still circumscribes the school in the functional register of State apparatus. On the other hand, and as a consequence, once again was called into question the book's theoretical horizon, capable of substantiating the defence of the school as res publica. On both fronts, the interview ends up shedding some light to a triple problematization: a) the impasses as to what arguing in favor of formal education nowadays means; b) the consequences of school practice being thought only according to a theoretical-pedagogical dimension, as the authors maintain; c) the constant tension existing between the actualization of historical experiences in the multiplicity of school context and the presupposition of thinking of a general school model.  Stemming from the interview,  either the opponents or the proponents of Masschelein and Simons' theses obtain new tools to rethink the ethico-political contours of In defence of the school.